Effects of extracorporeal carbon dioxide removal in facilitating ultra-protective ventilation strategies for patients with acute respiratory distress syndrome: a systematic review and meta-analysis - Zhen, Weifeng; Zhang, Xiaoning; Shi, Zhenhua; Zhu, Yu (Frontiers in Medicine, 2025)
BackgroundAlthough low tidal volume ventilation has been shown to reduce mortality in patients with acute respiratory distress syndrome (ARDS), overall mortality remains high (30%−40%). Ultra-protective ventilation (≤4 mL/kg predicted body weight) has the potential to further decrease ventilator-induced lung injury but may result in severe hypercapnia. Extracorporeal carbon dioxide removal (ECCO2R) could facilitate ultra-protective ventilation by alleviating carbon dioxide retention; however, supporting evidence remains limited.ObjectiveTo evaluate the efficacy of ECCO2R in enabling ultra-protective ventilation strategies in patients with ARDS.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library for studies published up to June 2025 that met predefined inclusion criteria. Primary outcomes included changes in gas exchange and ventilator settings 24 h after initiating ECCO2R. All analyses were performed using a random-effects model. Sensitivity and subgroup analyses were conducted to further explore the findings.ResultsFourteen studies involving 593 ARDS patients were included. ECCO2R significantly reduced driving pressure (weighted mean difference [WMD]: −3.70 cmH2O; 95% CI: −4.05 to −3.34; P < 0.001), plateau pressure (WMD: −3.26 cmH2O; 95% CI: −3.70 to −2.82; P < 0.001), and tidal volume (WMD: −1.68 mL/kg; 95% CI: −1.81 to −1.55; P < 0.001) at 24 h, while it increased positive end-expiratory pressure (WMD: 0.64 cmH2O; 95% CI: 0.44 to 0.85; P < 0.001). No significant changes were observed in PaO2/FiO2 ratio, pCO2, or pH (P > 0.05). The pooled 28-day mortality rate was 29% (95% CI: 19%−38%). Notable complications included bleeding (15%; 95% CI: 8%−21%), circuit clotting (19%; 95% CI: 13%−26%), and hemolysis (15%; 95% CI: 5%−25%).ConclusionECCO2R facilitates the implementation of ultra-protective ventilation by significantly improving respiratory mechanics and mitigating the hypercapnia that would otherwise result from ultra-low tidal volumes. However, its use is associated with a notable risk of device-related complications, necessitating careful patient selection and expert management.Systematic review registrationINPLASY platform (registration number: INPLASY202570067.